Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

6(x - 6) + x = 7(x - 7) + 13​

Sagot :

6x-36 +x=7x-49+13
7x=7x
Infinite solutions for x
trubio

Answer:

X = All Real Numbers

Step-by-step explanation:

Distribute: (6)(x) + (6)(−6) + x = (7)(x) + (7)(−7) +13

Multiply: 6x + −36 + x = 7x + −49 + 13

Combine like terms: (6x + x ) + (−36) = (7x) + (−49 + 13)

Simplify: 7x + −36 = 7x + −36

7x − 36 = 7x −36

Subtract 7 from both sides: -36 = -36

Add 36 to both sides: 0 = 0